Long-term durability of unidirectional glass-carbon/epoxy hybrid composites - Shan, Ying. (2008)
Based on a 2D shear lag model, a computer simulation program has been developed to model the tensile fracture, static and cyclic fatigue process of unidirectional hybrid composites. It is found this simulation model is capable to address certain phenomenon of the hybrid composites.